2019
DOI: 10.1111/acer.14202
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Chronic Heavy Alcohol Consumption in Male Rhesus Macaques Suppresses Cancellous Bone Formation and Increases Bone Marrow Adiposity

Abstract: Background: Chronic heavy alcohol consumption is an established risk factor for bone fracture, but comorbidities associated with alcohol intake may contribute to increased fracture rates in alcohol abusers. To address the specific effects of alcohol on bone, we used a nonhuman primate model and evaluated voluntary alcohol consumption on: (i) global markers of bone turnover in blood and (ii) cancellous bone mass, density, microarchitecture, turnover, and microdamage in lumbar vertebra.Methods: Following a 4-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…For skeletal system, low dosage of ethanol might be beneficial but high levels of ethanol consumption resulted in turnover imbalance where bone resorption exceeded formation . A very recent study indicated that a high dose of ethanol mainly decreased the function of osteoblast, without a significant impact on osteoclast activity . Our pilot study, as well as some others’, revealed that both trabecular and cortical bone were sensitive to long‐term and high‐dose ethanol .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…For skeletal system, low dosage of ethanol might be beneficial but high levels of ethanol consumption resulted in turnover imbalance where bone resorption exceeded formation . A very recent study indicated that a high dose of ethanol mainly decreased the function of osteoblast, without a significant impact on osteoclast activity . Our pilot study, as well as some others’, revealed that both trabecular and cortical bone were sensitive to long‐term and high‐dose ethanol .…”
Section: Discussionsupporting
confidence: 60%
“…2,[58][59][60] A very recent study indicated that a high dose of ethanol mainly decreased the function of osteoblast, without a significant impact on osteoclast activity. 61 Our pilot study, as well as some others', revealed that both trabecular and cortical bone were sensitive to long-term and high-dose ethanol. 12,62 Intriguingly, it was demonstrated that in the rat model, cortical bone was more vulnerable to high dose of ethanol than trabecular bone.…”
Section: Discussionmentioning
confidence: 48%
“…This variation might be attributed to the different biological responses of relevant bone cells trying to repair necrotic tissue 54 , re ecting distinct effects of these two etiologies. It has been proposed that glucocorticoid and alcohol reduce femoral artery perfusion through mechanisms such as vascular endothelial injury and microvascular thrombosis 55,56 . They can also induce the formation of intramedullary fat, which increases the pressure in the bones, leading to venous congestion and blocked arteries 19,57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings from a study on voluntary chronic heavy alcohol consumption in male rhesus macaques revealed that voluntary chronic heavy alcohol consumption reduces cancellous bone formation in lumbar vertebra by decreasing osteoblast-lined bone perimeter, a response associated with an increase in bone marrow adiposity (90).…”
Section: Mood Disorders (Bipolar Disorder Cyclothymic Disorder and Dmentioning
confidence: 99%